L’imaginaire technique et le savoir dans les journaux de bandes dessinées pour la jeunesse de 1946 à 1969 - Irène Langlet (Comicalités)
Comics magazines for young people are an excellent field for the examination of the technical imaginary, especially if taken as a global media language that reveals a genuine way of reading, both sophisticated in its logic and spontaneous in its practices. From the immediate post-war years to the end of the 1960s, these magazines served as a particularly powerful vector for the cultural dynamics of the so-called “Trente Glorieuses”. They provide an opportunity to observe how this was a genuine social project requiring a profound change in mentalities, and not simply a period of mechanically cumulative progress. The article shows this in four fundamental topics: a segregation of social genders, through the exclusion of girls from the technical imaginary; a division of social classes in access to knowledge; the improvement of powerful templates for visual and textual enunciation; and finally, a specific involvement in the grand narrative of progress, through the construction of the futurist regime of historicity—even and especially when it is not merged with science fiction.